Innovations Towards Sustainability Conditions and Consequences - Lehmann-Waffenschmidt, Marco; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2007)
The volume contains eight articles together with comments by twenty authors and discussants on the topic of innovations and sustainability. It provides a competently written, balanced and differentiated state-of-the-art insight into the relation between innovations and sustainability from the perspective of evolutionary economics. The scope of the contributions encompasses the technological, social, organizational, and political dimensions of the topic. Each article is discussed by a competently written commentary providing a critical evaluation and relating it to the relevant literature. Particular interest lies on the issues of steering opportunities and path formation capabilities by decentralized agents, or governmental institutions from the viewpoint of evolutionary economics.
New Approaches to Environmental Innovation Policy -- Windows of Opportunity for Radical Technological Change in Steel Production and the Influence of CO2 Taxes -- Comment: Approaches to the Modelling of Innovations for Sustainable Economic Systems -- Environmental Innovation Policy. Is Steering Innovation Processes Possible? -- Comment: Moderating Instead of Steering? -- Transition Management in the Electronics Industry Innovation System: Systems Innovation Towards Sustainability Needs a New Governance Portfolio -- An Example of a “Managed Transition”: The Transformation of the Waste Management Subsystem in the Netherlands (1960–2000) -- Comment: Management of Industrial Transformation: Potentials and Limits from a Political Science Perspective -- Innovations and Sustainability -- Leading Innovations to Sustainable Future Markets -- Comment: Sustainable Future Markets and the Formation of Innovation Processes -- Directional Certainty in Sustainability-Oriented Innovation Management -- Comment: Innovation Ability and Innovation Direction -- Arrangements in Society and Economy Towards Sustainability -- Deceleration — Revealed Preference in Society and Win-Win-Strategy for Sustainable Management. Concepts and Experimental Evidence -- Comment: Deceleration as a New Paradigm of Economic Science? -- Assessment Criteria for a Sustainability Impact Assessment in Europe -- Comment: Regulatory Choice and Responsive Regulation for Sustainability.
Keywords: Environmental economics; Economic policy; Economic growth; Environmental Economics; Economic Policy; Economic Growth